(3cJGH aj Gdabgs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3cJGH GdWgGQI hGQcGfg CQHYI, GdChd aj GdejGg LeYg HGYJHGQ JYOO CaQGOg hGdeQGO HgG GdCYes
(3BNQgG (B:s
(3BNQgG(B: (3hgh eMehd Ydi GdfOH LeYG (B... (3Cfj CMH Cf CVY hLgj aj ehVY JOd hjdMb HGdGfNaGV HGdGQJaGY YfO LeGYI ddehKbs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis